Strengthening conflict sensitivity in Kenya’s county climate change fund - Medina, Leonardo; Schapendonk, Frans; Jaskolski, Martina; Osumba, Joab; Jebiwott, Alice; Mutuku, Munini; Takaindisa, Joyce; Giti, Daniel (2025)
Governments, particularly those facing compounding climate vulnerability and conflict-related risks, must proactively address the potential unintended consequences of climate actions. Doing so requires strengthening existing adaptation instruments by mainstreaming conflict sensitive approaches, so that adaptation efforts are able to contribute to sustaining peace or, at the very least, do not ‘do harm’ by exacerbating existing conflict drivers. This policy brief shares key findings and recommendations from a joint study by the Adaptation Consortium (ADA) and the Alliance of Bioversity International – CIAT (the Alliance). The analysis focused on Kenya’s County Climate Change Fund (CCCF) mechanism. It evaluated whether the CCCF is designed, implemented, and monitored in ways that: 1) prevent new conflicts; 2) support peaceful ways of solving disagreements; and 3) use climate actions as opportunities to build peace. This policy brief summarizes the results from the analysis, which included Wajir, Isiolo and Kitui counties as case studies.